Pretreatment Metabolic Parameters Measured by 18F-FDG PET to Predict the Pathological Treatment Response of HCC Patients Treated With PD-1 Inhibitors and Lenvatinib as a Conversion Therapy in BCLC Stage C - Wang, Guanyun; Zhang, Wenwen; Chen, Jiaxin; Luan, Xiaohui; Wang, Zhanbo; Wang, Yanmei; Xu, Xiaodan; Yao, Shulin; Guan, Zhiwei; Tian, Jiahe; Lu, Shichun; Xu, Baixuan; et al. (Frontiers in Oncology, 2022)
Objectives: This study aimed to assess the pretreatment 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) as a predictor of the pathological treatment response (PTR) of hepatocellular carcinoma (HCC) patients treated with PD-1 inhibitors and lenvatinib as a conversion therapy in BCLC stage C. Methods: All patients (n=20) underwent pretreatment 18F-FDG PET/CT and were treated with conversion therapy and surgery. Patients were categorized into responders (n=9) and non-responders (n=11) according to PTR. The parameters of PET/CT, including lesion size, SUVmean (mean standard uptake value), MTV (metabolic tumor volume), TLG (total lesion glycolysis), SUVpeak (peak standard uptake value), and TLR (tumor-to-normal liver standardized uptake value ratio), were calculated. The diagnostic efficacy was evaluated by receiver operating characteristic analysis (ROC). PTR was compared with pretreatment PET/CT parameters by using Spearman correlation analysis. The patients were followed up. Results: There was significant difference in TLR (5.59±1.90 vs. 2.84±1.70, respectively; P=0.003) between responders and non-responders, with the largest area under the curve (sensitivity=100%, specificity=72.7%, AUC=0.899, 95%CI: 0.759-1.000, optimal diagnostic threshold of 3.09). The relationship between 18F-FDG PET/CT parameters and PTR indicated TLR was moderately and positively correlated with pathological treatment response, with correlation coefficients (rs) of 0.69 (P＜0.01). During the follow-up, no patients died, and tumor recurrence was found in 1 of the responders (11.1%). In all 11 non-responders, tumor recurrence was found in 6 patients (54.5%) and 4 patients (36.4%) died. Conclusions: TLR may be a powerful marker to predict PTR of HCC patients with BCLC stage C who were treated with conversion therapy.